PENERAPAN MEDIA QUIZLET UNTUK KETERAMPILAN MENULIS KALIMAT SEDERHANA BAHASA JERMAN KELAS XI SMAN 1 MENGANTI - Sholikha, Ekha Fatikhatus; Dwi Imroatu Jualikah, (LATERNE, 2024)
Writing skills are an essential part of learning German and should be developed effectively. Based on discussions with the German language teacher, it was observed that the low writing proficiency of students in class XI-7 was linked to the limited variety of teaching media used in lessons, particularly for writing activities. To address this issue, Quizlet was introduced as a learning tool. This study aimed to examine how Quizlet was implemented and to evaluate its impact on improving students’ ability to write simple sentences in German at SMAN 1 Menganti. The research adopted a qualitative approach, presenting results in descriptive form. Findings revealed significant improvements through the use of Quizlet. During the first session, observation scores reached 16 points (66.67%), categorized as “good,” and rose to 20 points (83.33%) in the second session, categorized as “very good.” Additionally, students’ writing test scores showed noticeable improvement from the first test to the second. In conclusion, Quizlet proves to be an effective medium for enhancing students’ skills in writing simple German sentences, particularly when supported with random vocabulary exercises. Keywords: Quizlet, writing skills, learning outcomes, German language.